DEVELOPMENT OF MATHEMATICAL LEARNING DEVICES BASED ON THE POE (PREDICTION, OBSERVATION, EXPLANATION) MODEL IN THE MATERIAL OF CONSTRUCTING FLAT SIDE SPACES - Faisal Bakti; Rezi Ariawan (UIR PRESS, 2021)
Mathematical creative thinking is the ability to produce varied answers or ideas to solve problems in mathematics. This study aims to build a valid learning device on flat-sided geometry using the POE model (Prediction, Observation, Explanation). The learning tools developed were syllabus, lesson plans, and LKPD on the flat side space building material. This type of research is development research with the ADDIE model, modified into three stages (Analysis, Design dan Development) without the implementation and evaluation stages. The research data collection instrument was a learning device validation sheet in a syllabus, lesson plans, and LKPD. Analysis of the data used is descriptive data analysis that describes the level of validity of the product. This study yielded a valid syllabus, lesson plans, and LKPD with 83.65%, 87.86%, and 86.31%, respectively. This study concludes that the Development of mathematical learning tools based on the POE model on the flat-sided geometry material has been tested for validity